Strategic interaction and donor policy determination in a domestic setting - S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper examines some of the issues associated with the aid donor process arising from the theory of agency or principal-agent models and endogenous policy determination. The principals may be viewed as legislators and the agents as the aid agency. In addition to adverse selection and moral hazard the paper considers intrinsic sources of motivation for agents and the trade-off between adverse selection and moral hazard. It also considers multiple task agents, and where there are many principals with divergent objectives. The principals might be better off by making the tasks more complementary and trading in their differing objectives. The paper also considers the formation of aid policy via median voter outcomes, lobbying with contributions and also in the presence of altruism. Finally, problems associated with signalling commitment to optimal policies are considered.
Keywords: H60; O11; O12; O19; 330; aid effectiveness; political processes; endogenous policy formation; Entwicklungshilfe; Prinzipal-Agent-Theorie